Algorithm for developing a system for public participation in physical culture and sports activities - Sedochenko, S.V.; Maslova, I.N.; Ezhova, A.V. (Theory and Practice of Physical Culture, 2025)
Objective of the study is to develop a comprehensive algorithm for effectively integrating various categories of citizens (focus groups) into the process of systematic physical education and sports (PES) activities, based on a comprehensive analysis of successful domestic experience gained as a result of implementing relevant measures in the constituent entities of the Russian Federation. Methods and structure of the study. The research was conducted by studying and analysing the results of practical activities of PES institutions operating in the constituent entities of the Russian Federation, in accordance with the provisions of Orders of the Ministry of Sport of the Russian Federation No. 175 of 1 March 2019 and No. 171 of 3 March 2022. Results and conclusions. It has been established that in order to involve the population in PES activities, it is recommended to follow a phased approach. The initial stage of the proposed model is the formation of an interdepartmental working group to determine the strategy and objectives for involving the population in PES activities. This is followed by planning based on regulatory and legal documents. The third stage involves selecting suitable types of physical education and sports activities, taking into account the resources of the region. The fourth stage involves promoting PES with a focus on the age and psychological characteristics of the target audience. The final stage is the implementation of innovative solutions that have been tested by successful regional projects. The above-described comprehensive algorithm for involving the population in systematic PES activities is common to all categories of the population, with specific features for each focus group.